Surface integrity after mechanical hardening of various aluminium alloys - Žagar, Sebastjan (Strojniški vestnik, 2011)
The paper presents two types of aluminium alloys, EN AW 2007 and EN AW 6082, treated by shot peening in which the surfaces of the metals were subjected to cold deformation under different treatment conditions. For this purpose, S170 steel particles with a diameter of 0.5 mm and a hardness of 56 HRC were used with different air pressures and mass flows, providing Almen intensity levels between 10A and 28A. The treated surfaces were studied in terms of surface integrity at macro- and microscopic levels, and the surface roughness, microhardness profiles, and residual stresses of each treated surface layer were recorded. Research results reveal significant differences between the properties recorded in the surface integrity examination, which are based on the selected shot peening parameters. This means that these parameters substantially impact the surface conditions and the surface layer. The microscopic analysis confirmed that the sharpest treatment conditions result in surface deformations which may cause cracks and subsequently lead to the mechanical part's collapse.
Keywords: aluminijeve zlitine; aluminium alloy; aluminium alloys; hrapavost površine; materiali; microhardness; mikrotrdota; residual stresses; shot peening; surface integrity; topografija površine; udarno utrjevanje; zaostale napetosti